The effects of acute leucine or leucine–glutamine co-ingestion on recovery from eccentrically biased exercise - Mark Waldron (Amino Acids, 2018)
This study investigated the effects of leucine or leucine + glutamine supplementation on recovery from eccentric exercise. In a double-blind independent groups design, 23 men were randomly assigned to a leucine (0.087 g/kg; n = 8), leucine + glutamine (0.087 g/kg + glutamine 0.3 g/kg; n = 8) or placebo (0.3 g/kg maltodextrin; n = 7) group. Participants performed 5 sets of drop jumps, with each set comprising 20 repetitions. Isometric knee-extensor strength, counter-movement jump (CMJ) height, delayed-onset muscle soreness (DOMS) and creatine kinase (CK) were measured at baseline, 1, 24, 48 h and 72 h post-exercise. There was a time × group interaction for isometric strength, CMJ and CK (P < 0.05), with differences between the leucine + glutamine and placebo group at 48 h and 72 h for strength (P = 0.013; d = 1.43 and P < 0.001; d = 2.06), CMJ (P = 0.008; d = 0.87 and P = 0.019; d = 1.17) and CK at 24 h (P = 0.012; d = 0.54) and 48 h (P = 0.010; d = 1.37). The leucine group produced higher strength at 72 h compared to placebo (P = 0.007; d = 1.65) and lower CK at 24 h (P = 0.039; d = 0.63) and 48 h (P = 0.022; d = 1.03). Oral leucine or leucine + glutamine increased the rate of recovery compared to placebo after eccentric exercise. These findings highlight potential benefits of co-ingesting these amino acids to ameliorate recovery.